2023
DOI: 10.1021/acssuschemeng.2c05497
|View full text |Cite
|
Sign up to set email alerts
|

Technical, Economic, and Environmental Comparison of Closed-Loop Recycling Technologies for Common Plastics

Abstract: Over 400 million metric tons of plastic waste are generated globally each year, resulting in pollution and lost resources. Recycling strategies can recapture this wasted material, but there is a lack of quantitative and transparent data on the capabilities and impacts of these processes. Here, we develop a data set of material quality, material retention, circularity, contamination tolerance, minimum selling price, greenhouse gas emissions, energy use, land use, toxicity, waste generation, and water use metric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 35 publications
(88 reference statements)
0
91
0
Order By: Relevance
“…To date, different methods have been investigated in previous studies, , which require further analysis of the technical properties (e.g., melt flow index, viscosity, etc.) of rPE basic/advanced . …”
Section: Resultsmentioning
confidence: 99%
“…To date, different methods have been investigated in previous studies, , which require further analysis of the technical properties (e.g., melt flow index, viscosity, etc.) of rPE basic/advanced . …”
Section: Resultsmentioning
confidence: 99%
“…The technology remains costly. One 2023 estimate by Gregg Beckham, a chemical engineer at the US National Renewable Energy Laboratory in Golden, Colorado, and his colleagues suggest that enzymatically recycled PET might currently cost around twice as much as the virgin product, and around four times as much as the mechanically recycled one; it also uses more energy and emits more greenhouse gases than does mechanical recycling 4 .…”
Section: Plastics Pollution Is a Transboundary Problem "mentioning
confidence: 99%
“…228 Over the last few years, several TEA and LCA studies have been published on the recycling of commercial polymers. 33,[229][230][231][232][233][234][235][236] In a recent example, the LCA of an exploratory, lab-scale synthetic process for the upcycling of poly(acrylic acid) revealed a 10-fold decrease in global warming potential (kg CO 2 kg −1 ) and cumulative energy demand (MJ kg −1 ) when an acid-catalyzed hydrolysis approach was employed vs. a base-mediated route. 237 The study revealed key method optimization parameters to minimize the impact on the environment at an industrial scale, which may have been overlooked in a lab-scale study that excluded LCA.…”
Section: Economic and Environmental Assessments In Dcvc-based Polymer...mentioning
confidence: 99%